The design of the layout and placement of goods within an automotive spare parts warehouse - Jaisai, Sakarn; Pongsathornwiwat, Akkaranan; Sukmok, Jugkarin (Journal of Applied Statistics and Information Technology, 2024)
This research aims to investigate the methods of product assignment to design an optimal layout and storage location of automotive spare parts in a warehouse. The objective is to reduce the travelling distance of pickers during the picking process. This study compares three models: 1) Class-based ABC layout, which groups products by picking frequency; 2) Optimal-based layout, which uses linear programming, so-called, Storage Location Assignment Problem to determine optimal storage locations; and 3) Association-based layout, which utilizes association rules to design the warehouse layout with the idea that the products that usually pick together must place close to each other. The results indicate that the layout utilizing Association Rules in conjunction with ABC classification is the most suitable, as it minimizes the walking distance for pickers.